2010
DOI: 10.1016/j.febslet.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of copper site properties by remote residues determines the stability of plastocyanins

Abstract: a b s t r a c tThe metal cofactor determines the thermal stability in cupredoxins, but how the redox state of copper modulates their melting points remains unknown. The metal coordination environment is highly conserved in cyanobacterial plastocyanins. However, the oxidised form is more stable than the reduced one in thermophilic Phormidium, but the opposite occurs in mesophilic Synechocystis. We have performed neutral amino-acid substitutions at loops of Phormidium plastocyanin far from the copper site. Notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Plastocyanin peaks tend to be broader, as expected for either a distribution of tunneling distances between the protein copper center and the electrode surface, or for a distribution of environments of the adsorbed protein [16]. Standard potential values of the immobilized proteins at 20°C (see Table 1) are~20 mV more positive (in the case of plastocyanin), or more negative (in the case of azurin), than their reported values in solution [17,18]. These standard potential shifts indicate a further stabilization of the reduced form of plastocyanin and of the oxidized form of azurin, upon adsorption at the graphite surface.…”
Section: Methodsmentioning
confidence: 79%
“…Plastocyanin peaks tend to be broader, as expected for either a distribution of tunneling distances between the protein copper center and the electrode surface, or for a distribution of environments of the adsorbed protein [16]. Standard potential values of the immobilized proteins at 20°C (see Table 1) are~20 mV more positive (in the case of plastocyanin), or more negative (in the case of azurin), than their reported values in solution [17,18]. These standard potential shifts indicate a further stabilization of the reduced form of plastocyanin and of the oxidized form of azurin, upon adsorption at the graphite surface.…”
Section: Methodsmentioning
confidence: 79%
“…According to their T m values, the oxidized form of Pho -Pc is more stable in solution than the reduced one, whereas the mesophilic variant shows the opposite trend, in agreement with previous works. 6,7,11,15 Interestingly, the V48I mutation increases the thermal stability of Syn -Pc. In particular, the oxidized V48I mutant is characterized by a higher T m value than the oxidized Syn -Pc WT protein, whereas the T m values of the reduced mutant and WT proteins were similar.…”
Section: Resultsmentioning
confidence: 98%
“…This indirect control was evident when inducing a thermal destabilization of the thermophilic protein after introducing a single mutation in the east patch . Further X-ray absorption spectroscopy investigations revealed that this mutation induces a subtle change in the local geometry of the Cu-binding site, which then causes the thermal stabilization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its thermostability has also been probed by spectroscopic techniques in a broad temperature range. 47,48 Based on these findings, this protein appears to be a good candidate to assess the influence of temperature on its ET kinetics.…”
Section: Toc Graphicsmentioning
confidence: 99%